2000
DOI: 10.1054/bjoc.1999.1012
|View full text |Cite
|
Sign up to set email alerts
|

Markers of bone turnover for the management of patients with bone metastases from prostate cancer

Abstract: Prostate cancer is the most common malignancy in elderly men and is often complicated by osteosclerotic metastases. Bone scintigraphy is commonly used to assess the extent of bone metastases; its use is limited in monitoring of treatment efficacy because it is an expensive, time-consuming technique that does not reflect the rapid skeletal response to therapy (Coleman, 1998). The bone scan flare response following successful therapy also reduces the value of bone scanning in the early monitoring of treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(137 citation statements)
references
References 57 publications
6
128
1
2
Order By: Relevance
“…In prostate cancer patients with clinical osteoblastic lesions, blood and urinary levels of bone resorption markers are often elevated [48]. Clinical trials have suggested that blocking osteoclastic bone resorption reduces related skeletal events in prostate cancer patients [49].…”
Section: Osteoblastic Bone Metastasismentioning
confidence: 99%
“…In prostate cancer patients with clinical osteoblastic lesions, blood and urinary levels of bone resorption markers are often elevated [48]. Clinical trials have suggested that blocking osteoclastic bone resorption reduces related skeletal events in prostate cancer patients [49].…”
Section: Osteoblastic Bone Metastasismentioning
confidence: 99%
“…An increase in markers of bone formation suggests the development of osteoblastic secondaries, whereas increases in markers of bone resorption suggest the development of lytic lesions. 43,44 These two processes frequently coexist in metastatic bone lesions. Bisphosphonate therapies have been shown to reduce markers of bone turnover and the number of skeletal-related events in individuals with metastatic prostate carcinoma.…”
Section: Noninvasive Markers Of Bone Turnover In Normal Men and In Mementioning
confidence: 99%
“…25 Other bone markers, such as serum osteocalcin and serum type I procollagen Cpropeptide, are also indicators of osteoblast activity; nevertheless, none of these other markers are specific biomarkers for bone metastasis. 26,27 In the current study, higher miR-141 levels indicated a higher number of bone lesions, which suggests that we may be able to use serum miR-141 as a specific marker for bone metastasis.…”
Section: Elevated Levelsmentioning
confidence: 52%